2017
DOI: 10.1002/hbm.23582
|View full text |Cite
|
Sign up to set email alerts
|

Robust presurgical functional MRI at 7 T using response consistency

Abstract: Functional MRI is valuable in presurgical planning due to its non‐invasive nature, repeatability, and broad availability. Using ultra‐high field MRI increases the specificity and sensitivity, increasing the localization reliability and reducing scan time. Ideally, fMRI analysis for this application should identify unreliable runs and work even if the patient deviates from the prescribed task timing or if there are changes to the hemodynamic response due to pathology. In this study, a model‐free analysis method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…55 , 56 Further studies demonstrated the usefulness and reliability of 7 tesla BOLD fMRI for presurgical planning. 57 , 58 Therefore, future studies are highly warranted to replicate our findings on a larger scale including CVR mapping and high-field or ultra-high-field BOLD fMRI. The model for calculation of OEF has also several limitations.…”
Section: Discussionmentioning
confidence: 79%
“…55 , 56 Further studies demonstrated the usefulness and reliability of 7 tesla BOLD fMRI for presurgical planning. 57 , 58 Therefore, future studies are highly warranted to replicate our findings on a larger scale including CVR mapping and high-field or ultra-high-field BOLD fMRI. The model for calculation of OEF has also several limitations.…”
Section: Discussionmentioning
confidence: 79%
“…In the next decade, magnetic field strengths are expected to go even higher than 7 T to reach 10 T or even 20 T [ 128 , 129 ]. This growing interest in UHF is already promoting the development of novel analysis methods to detect atypical brain activations [ 130 ]), to generate reliable patient-specific fMRI maps in cases with altered hemodynamic responses [ 131 ] or with huge head motion artefacts [ 132 ]. Thanks to the increase in BOLD sensitivity at UHF, presurgical mapping with fMRI at 1-mm isotropic resolution offers high BOLD sensitivity, accurate spatial mapping, and manageable data size.…”
Section: Discussionmentioning
confidence: 99%
“…[298][299][300][301][302] Thus far, however, UHF f MRI has been less extensively evaluated for clinical application, for example, for presurgical planning. 303,304…”
Section: Neuroradiologymentioning
confidence: 99%
“…In addition to the main applications of UHF fMRI to study neuronal activity at high spatial resolution, further promising areas of research are focused on fMRI of the cortical layers and columns 298–302 . Thus far, however, UHF fMRI has been less extensively evaluated for clinical application, for example, for presurgical planning 303,304 …”
Section: Functional Magnetic Resonance Imaging For Mapping Neuronal A...mentioning
confidence: 99%